Vocalisation of oriental magpie robin (Copsychus saularis linnaeus, 1758) in response to environmental factors in Peninsular Malaysia - Mohd Hanafi, Nur Shafinaz (2018)
Urbanisation has caused an increase in the anthropogenic noise and changes in environmental gradients in urban areas. These two variables have been shown to alter urban birds’ vocal communication structure in past studies. By using a common and vocally active bird species of urban areas in Malaysia, i.e. Oriental Magpie Robin (Copsychus saularis), this study described the territorial songs of the Oriental Magpie Robin; compared the bird’s vocalisation in relation to anthropogenic noise present in the urban, suburban and rural areas in Peninsular Malaysia; and assessed the effects of urban environmental factors on the bird’s vocalisation. The study was carried out in Kuala Lumpur, Putrajaya, Selangor and Negeri Sembilan between January and June 2017. Ambient factors (i.e. ambient noise, environment temperature, relative humidity and light intensity) and landscape factors (i.e. distances to building and major roads) were measured during sampling. Territorial songs of the bird were recorded and transcribed into spectrograms from which six parameters namely low frequency, high frequency, frequency ranges, length of strophe, number of elements per strophe, and time interval between strophes were derived. In urban areas, low frequency of song was found to increase significantly as compared to suburban and rural areas. The difference in noise, temperature and relative humidity in urban and suburban environment had led to both single and interaction effects towards the Oriental Magpie Robin’s song parameters, i.e. low frequency, length of strophe, time interval between strophes and number of element per strophe. The results showed that the Oriental Magpie Robin had adapted to urban condition by regulating and altering their frequency of song. This implied that the Oriental Magpie Robin have the ability to alter their vocalisations according to certain habitat condition. Such vocal alteration and adjustment are expected to be important in ensuring the efficiency in transmission of songs and it is a form of species behavioural adaptation in different habitat types and condition. This study also found that the Oriental Magpie Robin is likely to have opportunistic-switch plasticity and this may explain the reasons why certain urban bird species are less susceptible to urbanisation.